2012
DOI: 10.1093/jjco/hyr196
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year Follow-up of Triple-negative Breast Cancer Patients in Taiwan

Abstract: Objective: This study aimed to investigate whether triple-negative breast cancer has a worse prognosis; here, we present the 10-year follow-up results of triple-negative breast cancer patients in Taiwan. Methods: We identified 2858 breast cancer patients in Taiwan, of whom 416 (14.6%) had triple-negative breast cancer. Data used for analysis were derived from those breast cancer patients who were diagnosed between January 1996 and December 2006. Results: In the Kaplan -Meier analysis, tumor subgroup (triple-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Our multivariate Cox's regression analysis demonstrated that tumor size and axillary lymph node status were the main prognostic indicators for 7-year DFS and OS. These findings are in accordance with those of previous studies (8,19). Tumor subgroup (TNBC or non-TNBC) was identified as a significant prognostic factor of breast cancer in the univariate and multivariate survival analysis.…”
Section: Disease-free Survivalsupporting
confidence: 92%
See 1 more Smart Citation
“…Our multivariate Cox's regression analysis demonstrated that tumor size and axillary lymph node status were the main prognostic indicators for 7-year DFS and OS. These findings are in accordance with those of previous studies (8,19). Tumor subgroup (TNBC or non-TNBC) was identified as a significant prognostic factor of breast cancer in the univariate and multivariate survival analysis.…”
Section: Disease-free Survivalsupporting
confidence: 92%
“…Furthermore, the TNBC subgroup is associated with a higher risk of distant recurrence and mortality compared to its non-triple-negative counterparts, particularly during the first 3-5 years of follow-up (6). However, few studies have been conducted among non-Western populations (7) and the information on the Asian TNBC subtype remains confusing and limited (8). Kurebayashi et al (9) reported that Japanese patients with TNBC are mostly superimposable for disease-free survival (DFS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Such therapies are often used independently or in combination with other drugs, including bevacizumab and/or carboplatin . However, using chemotherapy has several limitations such as early recurrence, metastasis and multidrug resistance, an obstacle encountered ever more so due to rapidly mutating and evolving cancer cell populations . Currently, no targeted treatments are clinically approved for TNBC, and therefore, it is paramount to explore more targeted therapies using different treatment modalities such as photodynamic therapy (PDT) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally presence of lymph node metastasis was associated with worse disease-free survival. Similarly other studies from different populations underscore the influence of tumor size on survival for TNBC patients (23,24). A recent Asian study have demonstrated that tumor size and axillary lymph node status were the main prognostic indicators for 7-year DFS and OS in multivariate Cox's regression analysis (25).…”
Section: Resultsmentioning
confidence: 87%